A novel 20° x-ray angle shifter for superimposed canal separation - La Ongthong Vajrabhaya (2022)
Aim and objective: The purpose of this study was to evaluate the efficacy and frequency of a 20° angle Shifter in separating superimposed canals on multirooted tooth radiographs. Materials and methods: Radiographs from patients with 38, 44, and 39 of two-canal maxillary premolars, three-and four-canal mandibular molars, respectively, were taken at a horizontal 20° mesial and distal shift using the Shifter. The radiographs were evaluated by two examiners using the PowerPoint program. The percentage of distinctly separated canals in both shifted radiographs was analyzed using the Chi-square test (p = 0.05). The strength of agreement between each examiner (intra and inter) was evaluated using kappa statistics (p < 0.05). Results: The percentage of acceptable radiographs using the mesial and distal shift for both examiners was similar for maxillary premolars. However, the distal and mesial shift was superior compared with the mesial and distal shift in separating the root canals in three-and four-canal mandibular molars, respectively. The strength of agreement between examiners evaluated using kappa statistics (p < 0.05) was substantial-almost perfect. Conclusion: The Shifter efficiently separates superimposed canals. The advantage of the Shifter is the precise radiograph angle taken and at the same position during the multiple steps requiring radiographs in endodontic treatment. Clinical significance: The same position of the tooth on the multiple-step radiographs in endodontics is the benefit of this novel shifter.